MaryKay.Manda / Aiman Amanda Syahirah Herman - Herman, Aiman Amanda Syahirah (2021)
This semester, all students enrolled in the Entrepreneurship course must select one item. This study is aimed at evaluating and observing the reputation of the company as to the marketing method by which they wish to make the consumer more aware of the products they have sold. One of the greatest strategies of the firm is through social media which is Facebook to attract and acquire a customer. Furthermore, the analysis demonstrates how often the corporation promotes and markets its product on social media, specifically Facebook. Facebook has been chosen, and now more individuals of all ages utilize Facebook. In any business, a variety of tactics are required to market the commodity. In Facebook posts, teasers, hard sells, and even soft sells are used. This is due to the fact, that social media is an efficient means of communicating with clients. The more businesses that approach the audience, the more likely it is that the conversion company will start a two-way discussion. Even though Facebook offers a wide range of advertisements, it can assist businesses in reaching their target clientele more effectively than others. This will assist the organisation in meeting its revenue targets. The product they sell to their customers is likewise growing popularity. The Facebook link increases the likelihood that the company and its clients will acquire and retain customers.